Subungual glomus tumor: an uncommon cause of median canaliform nail-dystrophy of Heller - Mrinal Gupta, Vikas Sharma; Vikram K. Mahajan; Ravinder Singh (Our Dermatology Online, 2014)
Glomus tumor is an uncommon vascular tumor involving mostly subunguum of the thumb or the index finger. It commonly presents as a pink or purplish circumscribed nodule underneath the nail plate. Pain is paroxysmal in nature and precipitated often from exposure to cold or pressure/blunt trauma. Dystrophy of the nail plate occurs rarely. The described case, a 40-year-old woman, had dystrophic thumbnail ascribed to subungual glomus tumor that resembled median canaliform nail-dystrophy of Heller.